Analisis Pola Hidup Dan Dukungan Keluarga Pada Pasien Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Payung Sekaki (HEALTH CARE: JURNAL KESEHATAN, 2021)
Diabetes Mellitus (DM) is a metabolic disease characterized by high blood sugar levels. Type 2 DM is themost common.The reason is due to an unhealthy lifestyle, several attempts to reduce trigger factors suchas regulating diet, weight control, exercising, monitoring blood sugar, directed diet, healthy and balancednutrition. In addition, family support also affects the quality of life of DM patients. The purpose of this studywas to describe the pattern of life (diet, physical activity) and family support in patients with type 2 diabetes.This research method used descriptive analytic with cross sectional design. Thesample of this study was131 patients who were taken based on the inclusion criteria using purposive sampling. Results: Most patients were aged 56-65 years (36.6%) and mostly suffered by men (52.7%), respondents who experienced complications (91.6%) and most suffered by men (99, 9%) while the type of complication is numbness(peripheral nephropathy) (69.5%). The patient's lifestyle showed a good lifestyle (81.7) and family supportshowed good family support (98.5). Conclusion: A good lifestyle can also be influenced by good familysupport so that it makes sufferers more enthusiastic to apply healthy patterns in daily life.